Enhancement of ionic conductivity and thermal stability of CaO-stabilised zirconia (CSZ) with MgO addition by scavenging effects. (16th November 2016) - Kim, S.; Kim, S.; Lee, H.; Seo, Y.; Kim, B.; Lee, H.
Abstract : The effects of magnesia (MgO) addition on the ionic conductivity and thermal stability of CaO-stabilised zirconia (CSZ) was investigated by structural and morphological analysis. MgO was added to CSZ using a solid-state reaction, and a secondary phase was not observed via XRD of all specimens sintered at 1600°C. However, Mg2 SiO4 and Mg-rich phases were detected in the microstructure of CSZ doped with 5 and 10 mol-% MgO, respectively. Ionic conductivity increased with an increase in MgO content, and CSZ doped with 5 mol-% MgO exhibited a maximum value of 0.819 S cm −1 measured at 1500°C due to the scavenging of Si impurities. The thermal diffusivity increased from 0.517 (CSZ) to 0.649 mm 2 s −1 (5 mol-% doped CSZ), and the thermal expansion coefficient of 0.5 mol-% doped CSZ was maximal at 9.855 μm/m°C. The value of mol-% doped CSZ decreased to 8.937 μm/m°C as it was affected by the Mg–Si phase formation.